Do consumers ‘Get the facts’? A survey of alcohol warning label recognition in Australia - Coomber, Kerri (BMC Public Health, 2015)
BACKGROUND: There is limited research on awareness of alcohol warning labels and their effects. The current study examined the awareness of the Australian voluntary warning labels, the ‘Get the facts’ logo (a component of current warning labels) that directs consumers to an industry-designed informational website, and whether alcohol consumers visited this website. METHODS: Participants aged 18–45 (unweighted n = 561; mean age = 33.6 years) completed an online survey assessing alcohol consumption patterns, awareness of the ‘Get the facts’ logo and warning labels, and use of the website. RESULTS: No participants recalled the ‘Get the facts’ logo, and the recall rate of warning labels was 16 % at best. A quarter of participants recognised the ‘Get the facts’ logo, and awareness of the warning labels ranged from 13.1–37.9 %. Overall, only 7.3 % of respondents had visited the website. Multivariable logistic regression models indicated that younger drinkers, increased frequency of binge drinking, consuming alcohol directly from the bottle or can, and support for warning labels were significantly, positively associated with awareness of the logo and warning labels. While an increased frequency of binge drinking, consuming alcohol directly from the container, support for warning labels, and recognition of the ‘Get the facts’ logo increased the odds of visiting the website. CONCLUSIONS: Within this sample, recall of the current, voluntary warning labels on Australian alcohol products was non-existent, overall awareness was low, and few people reported visiting the DrinkWise website. It appears that current warning labels fail to effectively transmit health messages to the general public.